2005
DOI: 10.1063/1.1879932
|View full text |Cite
|
Sign up to set email alerts
|

Experimental detection and theoretical characterization of the H2–NH(X) van der Waals complex

Abstract: The H2-NH(X) van der Waals complex has been examined using ab initio theory and detected via fluorescence excitation spectroscopy of the A(3)Pi-X(3)Sigma(-) transition. Electronic structure calculations show that the minimum energy geometry corresponds to collinear H2-NH(X), with a well depth of D(e)=116 cm(-1). The potential-energy surface supports a secondary minimum for a T-shaped geometry, where the H atom of NH points towards the middle of the H2 bond (C(2v) point group). For this geometry the well depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…III A and III B. As is expected 26 and shown in Fig. 4, the BSSE corrections reduce the binding energy by almost a factor of 2 and reduce the van der Waals bond length by about 5%.…”
Section: One-dimensional Radial Potential Energy Curvessupporting
confidence: 57%
“…III A and III B. As is expected 26 and shown in Fig. 4, the BSSE corrections reduce the binding energy by almost a factor of 2 and reduce the van der Waals bond length by about 5%.…”
Section: One-dimensional Radial Potential Energy Curvessupporting
confidence: 57%
“…Indeed, the van der Waals interactions of NH with rare gases [1][2][3][4] and small molecules [5][6][7] have been the object of detailed and careful theoretical and experimental studies over the past decades. Systematic investigations of the complexes of NH with Ar, He, and Ne or with small molecules such as NH or N 2 have yielded considerable information on structure and internal dynamics of van der Waals complexes.…”
Section: Introductionmentioning
confidence: 99%
“…8, is summarized in Table III, which includes the structural parameters obtained in similar calculations for the NH 3 and H 2 moieties. The calculated N¯H separation for the axial complex, 2.89 Å, compares closely with that recently calculated by Fawzy et al 16 for the HH¯NH complex, 2.85 Å. None of the distances between pairs of atoms in the NH 3 moiety was calculated to change by more than 0.001 Å from the corresponding distance for bonded and unbonded atom pairs obtained for uncomplexed NH 3 .…”
Section: Properties Of Binary Complexes Of Nh 3 With Hmentioning
confidence: 89%
“…Early experimental investigations of the complexation of H 2 by amorphous ice spurred a series of ab initio calculations, 11 16 reported a fluorescence excitation spectrum for the A 3 ⌸ − X 3 ⌺ − transition of the H 2¯N H complex. Their calculations predicted a binding energy of approximately 1.4 kJ/ mol ͑116 cm −1 ͒, as well as a secondary minimum for a T-shaped structure analogous to that of H 2¯H F. They suggested that the primary minimum is contributed by the complex with H 2 ͑j =1͒ and the secondary minimum by that with H 2 ͑j =0͒.…”
Section: Introductionmentioning
confidence: 99%